O exemplo, o milagre, a vida: a hagiografia e o culto de um santo minorita como reguladores sociais em uma comuna medieval italiana (Orvieto, séculos XII-XIV) - Felipe Augusto Ribeiro (2015)
This text deals with the relations between the worship of saints and the urban communities during the Italian thirteenth century. It focuses especially on the Dialogus sanctorum fratrum minorum, an hagiographic compilation produced in 1245 by an anonymous author, and in the case of Ambrose of Mass (1240), a friar dead in fame of holiness and reported by various other compilations. To investigate the problem of the great number of friars catalogued by these compilations, although not canonized, this work contextually chains these various compilations and approaches the Dialogus with other contemporary sources, analysing them within the theoretical field of Civic Religion concept. It starts from the hypotheses that these communities demanded new saints to benefit themselves from their sacredness and and its results of peace making and political congregation, while the Order of Friars Minor tried to respond to this demand producing new saints that, although rejected by the papacy, were embraced by municipalities and publicized as legitimate and effective saints. The convergence between that demand and this offer had benefited the Order itself as it claimed its powers of intervention and social regulation. In addition, these city governments would gain with the combat that these saints could do against heretics. The aim of this work is to describe and demarcate the places and roles of city governments, the friars and the papacy in the production, circulation and consumption of these sanctities. Its result shows that the holiness in question was important to its producers, sponsors and consumers because it standardized the social urban life proposing a holiness that expressed an exemplary life and offered a miraculous power affordable only by emulating this model of life. This standardization had, as effect, the regulation of moral behaviours and the consequent social conformation of townspeople resulting in in peace and social union, values much desired by communities as conflictual and unstable as those that this work deals with.